2014
DOI: 10.1186/1745-6215-15-325
|View full text |Cite
|
Sign up to set email alerts
|

Relating therapy for voices (the R2V study): study protocol for a pilot randomized controlled trial

Abstract: BackgroundEvidence exists for the effectiveness of cognitive behaviour therapy for psychosis with moderate effect sizes, but the evidence for cognitive behaviour therapy specifically for distressing voices is less convincing. An alternative symptom-based approach may be warranted and a body of literature has explored distressing voices from an interpersonal perspective. This literature has informed the development of relating therapy and findings from a case series suggested that this intervention was acceptab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…In terms of the change in these other brief targeted approaches, Freeman et al (2016) found using strategies to improve self-confidence a small reduction in negative schemas (Cohen's d = 0.24) and a moderate reduction in paranoia (d = 0.59). Hayward et al (2014), in a pilot randomised controlled trial of relating therapy, found a larger effect size of d = 1.30 on PSYRATS distress at end-of-therapy. Our much smaller case series would appear to compare favourably; however, larger studies need to be conducted before meaningful comparisons could be made.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In terms of the change in these other brief targeted approaches, Freeman et al (2016) found using strategies to improve self-confidence a small reduction in negative schemas (Cohen's d = 0.24) and a moderate reduction in paranoia (d = 0.59). Hayward et al (2014), in a pilot randomised controlled trial of relating therapy, found a larger effect size of d = 1.30 on PSYRATS distress at end-of-therapy. Our much smaller case series would appear to compare favourably; however, larger studies need to be conducted before meaningful comparisons could be made.…”
Section: Discussionmentioning
confidence: 95%
“…As a brief targeted intervention, it could be added as a module to other theoretically based approaches, which also have initial feasibility and acceptability (Freeman et al, 2016;Hayward et al, 2014). In terms of the change in these other brief targeted approaches, Freeman et al (2016) found using strategies to improve self-confidence a small reduction in negative schemas (Cohen's d = 0.24) and a moderate reduction in paranoia (d = 0.59).…”
Section: Discussionmentioning
confidence: 99%
“…The approach of Birchwood and colleagues provides a bridge between early formulation-based approaches centering on intra-psychological (cognitive, affective, and behavioral) processes and a new wave of relational approaches which focus on the interpersonal relationship between the voice-hearer and the voice Hayward et al 2014 ;. Relating therapy (Hayward et al 2009 ) specifi cally applies Birtchnell's ( 1996 ) interpersonal model to the voice-hearer relationship, identifying key interpersonal dimensions of power and proximity (Birtchnell 1996 ).…”
Section: Resultsmentioning
confidence: 99%
“…The use of a modular approach in the Feeling Safe Programme is helpful in its flexibility, allowing for the later addition of other theoretically underpinned approaches that may emerge as clinically useful (e.g. Hayward, Strauss and Bogen-Johnston, 2014 ; van den Berg et al, 2015 ; Lincoln, Hartmann, Kӧther and Moritz, 2015 ; Morrison et al, 2014 ). The baseline scores of a number of the trial patients reduced slightly over time – one interpretation is that the delusions were already beginning to recover, but our view, given the previous persistence of the delusions, is that this reflects the early stages of change triggered by the frequent and relevant assessments.…”
Section: Discussionmentioning
confidence: 99%